Modélisation du transport éolien dans le système plage-dune de la baie d'El Haouzia (côte atlantique marocaine) - Mohamed Chaibi; Mohamed Maanan; François Sabatier; Abdessamad Charif; Mohamed Ayt Ougougdal; Halima Ait Malek (Physio-Géo)
Coastal dunes raise a special problem to scientists because of the high dynamic nature of most beach-dune systems. Coastal dunes can change shape quickly and frequently due to the violence of winds and waves during storms. This study analyses and interprets spatial and temporal patterns in sediment volume changes in a beach-dune system using different aeolian transport formulas.During the measurements (24 campaigns), traps allowed to collect particles transported by the wind in order to determine the grains size and the critical shear velocity. For the grains size, the mode varies between 160 and 250 µm. The critical shear velocity is 0.23 m.s-1. Measured wind velocities range from 7.45 to 13.13 m.s-1. The transport flow varies between 0.19 and 1.14 kg.m-1.min-1. The measured transport rates were compared with the predictions of different models. The BAGNOLD-equation, using roughness length (zo) of 0.1 mm (S.M. ARENS, 1997) and adjustment length (K = 1.2), proved to have the best predictive ability: for every trap, the predictions are in the 95 percent confidence interval of the measurements (Root Mean Square = 30 %).The amount and direction of annual net transport have been computed with the BAGNOLD-equation. On the El Haouzia beach there is a positive transport flux in the direction of the dune field. This causes an annual increase of the average dune height of several centimetres. The used sand traps were compared.